Prognostic parameters in recurrent colorectal cancer: A role of control or restaging by FDG-PET/CT - Hancerliogullari, Oguz; Okuyucu, Kursat; Ince, Semra; Peker, Subutay; Arslan, Nuri (Vojnosanitetski pregled, 2021)
Background/Aim. Colorectal cancer ranks the third most frequent cancer in the world. Approximately 40% of the disease recurs after surgical resection. Determination of predictive parameters for recurrence may help in stratification of patients and contribute to patient management. There are still very few studies which sought factors to predict the recurrence of colorectal cancer. The aim of this study was to examine the predefined risk factors in metastatic development and evaluate clinical significance of 18F-fluorodeoxyglucose (FDG) uptake. Methods. The study was conducted with 56 patients for whom FDG-PET/CT (FDG-positron emission tomography/computed tomography) was requested for the suspicious recurrence or metastasis by routine conventional screening tests. Thirty three patients in whom recurrence/metastases were established with final histopathologic diagnosis formed the malignant group, and 23 patients with no recurrence/metastases formed the benign group. Risk factors [age, serum carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (Ca 19-9) levels, the maximum standardized uptake volume (SUVmax), tumor size (TS), CT/magnetic resonance imaging (MRI) findings, sex, primary tumor localization, lymphovascular invasion, perineural invasion (PNI), initial neoadjuvant therapy, lymph node initial metastasis (ILNM) excision, stage, tumor differentiation] were compared between these groups. Results. CEA, Ca 19-9, SUVmax, TS, PNI, ILNM, FDG uptake pattern, pattern of lesions on CT and tumor differentiation were found statistically significant by univariate analysis. After multivariate analysis, SUVmax and ILNM remained as the main risk parameters impacting recurrence/metastases. Mean SUVmax was 7.25 in the benign group, while it was 11.7 in the malignant group (p = 0.019). ILNM was present in 66.5% of patients in the malignant group, and in 30.5% of patients in the benign group (p = 0.015). For an estimated cut-off value of 6.3 and 12.5, respectively on ROC curve, the calculated specificities were 61% and 87%, respectively. Conclusion. ILNM and SUVmax are the main risk factors for recurrence of colorectal cancer and the patients with these factors must be followed up carefully. FDG-PET/CT is very sensitive for the detection of recurrence/metastases of colorectal cancer and SUVmax appears to improve its specificity.
Keywords: colorectal neoplasms; neoplasm staging; prognosis; radiopharmaceuticals; recurrence; sensitivity and specificity; tomography, emission-computed; tomography, x-ray computed